Low-level jets and their implications on air pollution: A review - Wei, Wei; Zhang, Hongsheng; Zhang, Xiaoye; Che, Huizheng (Frontiers in Environmental Science, 2023)
Low-level jets (LLJ) are a common phenomenon in the atmospheric boundary layer and have been reported worldwide. Additionally, they have considerable relevance in a series of fields. This review aimed to document their implications on air quality, specifically particulate matter, mineral dust, and ozone in recent literature focus on i) generalizing long-range advection of pollutants by the LLJs; ii) analysing vertical transport due to LLJ-enhanced turbulence mixing and the corresponding mechanisms for different pollutants; and iii) introducing the performance of state-of-the-art numerical models. Finally, we suggest that high-resolution spatiotemporal observations of the pollutants and turbulence must be conducted, and current parameterization schemes should be improved to better represent the LLJs and nocturnal boundary layer structures for reproducing the complicated interactions between the LLJs and pollutants.